A study of sustainable green current generated by the fluid-based triboelectric nanogenerator (FluTENG) with a comparison of contact and sliding mode. (August 2017) - Nahian, Syed Abu; Cheedarala, Ravi Kumar; Ahn, Kyoung Kwan
Abstract: Recently, the triboelectric nanogenerator (TENG) has become a well-known energy harvester for ambient-resource energy harvesting for which the contact electrification between two different materials is employed. Alternatively, research has been carried out on the fluid-based TENG (FluTENG) for the replacement of the conventional solid-based TENG due to the destruction of the active surface by a long mechanical rupture that reduces the triboelectrical effect. For the first time, a simple, eco-friendly, very economical, and novel DI (deionized)-water commercial-polytetrafluoroethylene (cPTFE)-based FluTENG with contact-separation (CS-FluTENG) and lateral-sliding (LS-FluTENG) modes has been developed for this paper. Here, we examined the dynamic interaction between water and solid contact for each mode. During the study of the surface morphologies for both the CS-FluTENG and the LS-FluTENG, an FE-SEM analysis showed expansions of the fibril lengths in the film network. Also, the mechanistic approach of water splitting and the way that a chemical reaction occurs with the cPTFE film during the contact electrification that have been proved by UV-spectroscopy, FT-IR, and XRD analyses were investigated in this manuscript. The contact-angle measurements revealed that the surface-hydrophobicity values of the films were decreased after the CS-FluTENG and LS-FluTENG experiments due to a roughness increment, and the fibril distance from the nodes was increased. The triboelectric-power density values reached up to 2.15 mW/m 2 for the CS-FluTENG and 0.8 mW/m 2 for the LS-FluTENG, respectively. Moreover, the instantaneous power reached up to 2.4  µW for the CS-FluTENG and 1.85  µW for the LS-FluTENG, respectively. Graphical abstract: Scheme1 . Schematic illustration of a fluid triboelectric nanogenerator. Highlights: A novel fluid based TENG(FluTENF) using DI water and cPTFE film is proposed. Lateral sliding and contact separation type FluTENG is compared and analyzed by FE-SEM analysis. The triboelectric power density is achieved upto 2.15 mW/m 2 for CS-FluTENG and 0.8 mW/m 2 for LS-FluTENG. The energy loss in CS-FluTENG is significantly higher than LS-FluTENG.